Interest Rate Policy of the Banque Centrale des Etats de l'Afrique de l'Ouest: International Currency Hierarchy, Monetary Base Coverage, and Bank Lending in the WAEMU - Florian Lampe (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2022)
While criticism of the post-colonial character of the CFA franc zone is intensifying, little research has yet been done on the concrete implications of this currency regime for the monetary policy of the two CFA central banks - and hardly any attention is being paid to these implications in the current political debate on the reform of the CFA franc zone. This is why the present article first addresses the autonomy of the interest rate policy of the Banque des Etats de l'Afrique de l'Ouest (BCEAO), which sets the key interest rate for the western part of the CFA zone countries. It can be seen here that, on the one hand, the BCEAO's response to the ECB's interest rate policy since 1994 is very largely compatible with the assumptions of the open-economy trilemma and, on the other, that the difference in interest rate levels cannot be explained using the traditional assumptions of interest rate parity theory. We thus have to have recourse to the post-Keynesian notion of the international currency hierarchy. The second part of the study first theoretically explores the monetary policy implications of the institutionally anchored requirement that 20 percent of the monetary base need to be covered by foreign exchange reserves. A descriptive analysis of the evolution of monetary aggregates then shows that the potentially restrictive effect of the monetary base coverage is presently not (yet) constraining commercial bank lending in the WAEMU.
Keywords: 330; CFA Franc; WAEMU; monetary policy; currency hierarchy; bank lending